here for a moment - an attempt to knowing the practice by practicing - Beau, Raphaël (Taideyliopiston Teatterikorkeakoulu, 2023)
...Knowing the practice by practicing… …(Under)standing performance by performing… …Learning how to facilitate by facilitating… …Learning to play by playing… This document is about an artistic practice I have been developing for the past five years, and more intensively for the past two years, during my studies in the Master’s Programme in Dance Performance at the Theatre Academy, University of the Arts Helsinki. It is an attempt to find words to better define this artistic practice. “here for a moment” both refers to a specific location in space (here) and a specific duration in time (for a moment). This document gives a framework to this practice which has its origins both in improvisation and instant composition. It attempts to capture what my practice is at this moment and where the practice happens. It is about finding the practice by practicing. It is about inviting the practice to a place within me, and let it grow from that place. The first chapter is an opening of the practice. It is an attempt to start writing: writing as practice and writing about the practice. It opens to the practice as I have been experiencing it during Uniarts opening ceremony in September 2022. It opens to the origin of this practice, to the place and to the human environment that allows the practice to grow. The second chapter is about the practice itself, a practice that does not have a name yet but which is finding its own name by being activated with words. This chapter is in dialogue with practices and writings from a choreographer-performer, a dancer-researcher and an associate professor of art History. Through their experience of “practice”, “writing” and “place”, they are opening ways for me to relate with the notions of writing and place when it comes to my own practice. The third chapter is about performance and performing and how my body and mind have found a place to experience them. This chapter is in dialogue with texts and practices from improvisation and instant composition practitioners and a dramaturge. It goes through the understanding I have been building about performance and performing, the combination of score and instant composition within a performance, and the notions of witness and public space when it comes to performance. The fourth chapter is about the practice when I open it to other practitioners. I have been opening this practice every week for one year now. Together with the making of the performance reproduced in various contexts, the open practice has become the second main outcome of my studies at Uniarts Helsinki. In this chapter I attempt to trace the history of the emergence of this open practice, through other practices that has informed it. I describe how facilitating an open practice has allowed a space for me to learn how to facilitate. The fifth chapter is another opening, From now on. It is about pushing towards and from the “now” in order to move forward. It is about acknowledging what happened during my Master studies at Uniarts Helsinki and how I can move on from that place.
Keywords: performance. performing. writing. layers. loops. on-going. talking. thoughts. spoken words. play. playfulness. actions. questions. learning. facilitating. practice. open practice. here. place. skin. body. state. scores. instant composition.; tanssi; performanssi; fi=tanssi|sv=dans|en=Dance Performance|